Development of a bio-inspired magnetic nanocomposite synthesized through semi-covalent imprinting for electrochemical determination of cholesterol in water samples - Peixoto Lins, Eduardo; Effting, Luciane; Maria Effting, Letícia; Del Pilar Taboada Sotomayor, Maria [UNESP]; Gava Segatelli, Mariana; Bail, Alesandro; Ricardo Teixeira Tarley, César (Wiley, 2023)
Fecal pollution in aquatic environments by analysis of fecal coliforms along with the determination of sterol compounds, such as cholesterol (CHO) has been extensively investigated. Thus, the development of an easier, cheaper, selective, and sensitive method for CHO monitoring in aquatic environments can be a valuable tool in contributing to the analysis of fecal pollution mainly in developing countries. In the present study, a voltammetric method aiming at CHO determination in aqueous media based on a magnetic molecular imprinted polymer (MMIP) sensor is proposed. The MMIP was synthesized on the surface of silica-coated magnetite, using CHO as a template covalently bound to 3-(triethoxysilyl)propyl isocyanate (ICPTES). A suspension of MMIP was prepared in ethanol and used to modify a graphite-epoxy composite magneto-actuated electrode (m-GEC). The indirect CHO determination was based on the decrease in the current of [Fe(CN)6]3−/4− redox probe in the presence CHO. Under optimized experimental conditions (Britton-Robinson buffer 0.01 mol L−1 at pH 7.0), the parameters of square wave voltammetry were optimized through the Doehlert matrix (amplitude of 111.2 mV, potential increase of 10.8 mV and frequency of 5.54 Hz). An analytical curve ranging from 0.51 up to 11.0 μmol L−1 was obtained with a limit of detection of 0.15 μmol L−1. The developed method was applied to the analysis of the lake water sample, and the accuracy of the method was confirmed by HPLC-DAD as a reference technique.
Keywords: aqueous samples; cholesterol determination; fecal pollution; graphite-epoxy composite magneto-actuated electrodes; voltammetry